Антология выдающихся достижений в науке и технике. Часть 48: Авиаконструктор Андрей Туполев и его свершения в самолетостроении - Баранов, М.И. (Електротехніка і електромеханіка, 2019)
Приведен краткий научно-истрический очерк о выдающемся советском авиаконструкторе Андрее Николаевиче Туполеве, ставшем одним из основоположников мирового самолетостроения. Описаны основные научно-технические достижения А.Н. Туполева в области самолетостроения, приведшие советскую военную и гражданскую авиацию на невиданные мировые высоты. Показано, что А.Н. Туполев является основателем известной в мире авиационной научной школы, воспитавшей многих видных в бывшем СССР авиаконструкторов. Под руководством великого авиаконструктора 20-го столетия А.Н. Туполева в СССР было разработано свыше 100 типов самолетов военного и гражданского назначения, 70 из которых изготавливались авиационной промышленностью страны серийно. A short scientifically-historical essay is presented about a prominent Soviet aircraft designer Andrey Nikolaevich Tupolev, becoming in the 20th century one of founders of Soviet and world aviation. Basic scientific and technical achievements of A.N. Tupolev indicated in area of airplane design, bringing Soviet military and civil aviation around to extraordinary world heights. Basic tactical and technical descriptions are described regarding created under his scientific and technical guidance of such known types of civil airplanes as ANT-25, Tu-104, Tu-134, Tu-154 and Tu-114, and also military airplanes of type Tu-2, Tu-16 and Tu-95. Short information is resulted about flying descriptions of the modern Russian supersonic strategic bomber of type Tu-160, created in 1980-th in the design bureau name after A.N. Tupolev. It is marked that under guidance of A.N. Tupolev over 100 types of airplanes of the military and civil setting were developed in the former USSR, 70 from which are produced by aviation industry of country serially.